The Impact of Socialization on Increasing The Understanding of Maintaining Physical Fitness in The Work Environment among Managers of The Nusa Indah Reading Park in The Bintan Coastal Area - Intasir M. Pemberdi; Siregar Eko Febri Syaputra; Sarkity Dios; Fernando Adam; Pratama Yudi (SHS Web of Conferences)
Physical fitness is a requirement in life to be healthier and able to carry out productive activities. Everyone needs good physical fitness, so they can carry out their work effectively and efficiently without experiencing significant fatigue. Likewise, in the world of work, good physical fitness is also very necessary to be able to complete work well, especially for the managers of the Nusa Indah Reading Park in Bakau Bay, Bintan Regency, there are still some reading park managers who don't know how to calculate a person's fitness level and how to maintain your own physical fitness. Based on the problems above, researchers are interested in seeing the level of understanding in maintaining fitness levels in the world of work among Nusa Indah reading park managers Based on the problems above, researchers are interested in seeing the level of understanding in maintaining fitness levels in the world of work among Nusa Indah reading park managers. Based on the problems above, researchers are interested in seeing the level of understanding in maintaining fitness levels in the world of work among Nusa Indah reading park managers.